Vice-Chairman of the Scientific and Organizing Committee, Radio Research Section, 3rd International Congress of European Communication Research and Education Association (ECREA), with theme, Transcultural Communication – Intercultural Comparisons, Hamburg - Gazi, Angeliki (My University, 2026)
Vice-Chairman of the Scientific and Organizing Committee